Implementasi Peraturan Menteri Agama RI Nomor 45 Tahun 2015 Tentang Disiplin Kehadiran PNS Di Lingkungan Kementerian Agama - Wan Hamdani Ismail; R. Hamdani Harahap; Kariono Kariono (Jurnal Administrasi Publik (Public Administration Journal), 2018)
In order to improve the administrative order, on the guidance of civil servants of the Ministry of Religious Affairs, the provision on discipline of Civil Servant attendance at the Ministry of Religious Affairs has been issued Regulation of the Minister of Religious Affairs No. 45 of 2015 on Amendment of Regulation of Minister of Religious Affairs No. 28 of 2013 on Discipline Environment Ministry of Religion. Implementation of Regulation of the Minister of Religious Affairs Number 45 of 2015 on Discipline of Civil Servant Attendance In the Ministry of Religious Affairs in Madrasah Ibtidaiyah Negeri Penanggangan Serdang Bedagai Regency viewed from the aspect of communication, resources, disposition and bureaucracy strutktur in general has been well implemented.